Východiská pre tvorbu priemyselnej politiky udržateľnej konkurencieschopnosti sklárskeho priemyslu Českej republiky - Slunčík, Peter; Lang, Helmut; Dvořáček, Jiří, 1947-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2010)
ABSTRACT The subject of this doctoral thesis is a framework for building an industrial policy for sustainable competitiveness of the glass industry in the Czech Republic. Industrial policy and competitiveness do not have commonly accepted definitions. Concepts on definitions differ across nations, regions, stage of development and over time -- in short or long time. Coming from these problems there are questions connected with horizontal or sectoral level of application. Globalization is a challenge for industry, the environmental issues alike. On one hand side is there enormous growth of costs on the other growth of business opportunities. Systemic approach to analysis of the complex of business environment brought progress to solve problems connected with articulation integrated levels. A complete analysis of the glass industry enables to understandnot only problems but also challenges driving the industry. Quality of political environment and mutual collaboration with all the actors is crusial for next development of succesful sustainable growth of the national economy. There is not the question if to do the industrial policy or not; the question is: how to do it?
Vedoucí práce: Helmut Lang
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2010
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2010
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations